An analysis of Corporate Social Responsibility in the Spanish energy sector: how it is presented, how it is perceived - Lasierra-Asún, Diana Victoria (Acciones e Investigaciones Sociales, 2021)
This paper analyzes the Corporate Social Responsibility of companies in the energy sector that are listed on the Ibex 35. It revolves around contrasting the stance taken by these companies on the policies of commitment to society in social or environmental terms, included in Corporate Social Responsibility theories, with the company’s own perception of these business actions. The question is whether these policies respond to a sophisticated marketing strategy, or instead constitute a true and real corporate commitment to issues that concern society as a whole.The study is organized to follow the Triple Bottom Line (economic, social and environmental concerns), while focusing on the social and environmental dimensions. To do this, two indices are developed and compared. The Sustainability Index, which collects the information provided in the company’s sustainability reports for a period of three years, and the Real Sustainability Index, which represents the perception of society in general, obtained from various sources external to the company itself.The analysis concludes that companies in the sector carry out actions that are perceived as insufficient in their social dimension while society expresses a more positive assessment of the environmental field. Therefore, it should be noted that the Social Responsibility policies implemented by the companies analyzed, especially in
Keywords: corporate social responsibility; sustainability report; sustainability indicators; business commitment and company objectives